An incarnation engaged worship and spirituality - EK Foshaugen (Acta Theologica)
Modern culture is sick with secularism resulting in a growing recognition permeating our culture that all life is at root spiritual. Whilst not necessarily recognised in Christian terms, there is a growing awareness and craving for spirituality. People are turning ro exotic cultures and esoteric practices in search of intimacy - a desire to experience human love and trust, meaning and purpose; and transcendence - recognition of the divine. Through developing a theology of spirituality and worship chis article attempts to define a practical theological theory for worship and spirituality. Worship and spirituality are incarnational engaged lifestyles that give voice to the nature, character and will of God and are reflected in the Christian's human activities of adoracion to God and action in the world. This incarnational engaged approach, expressed in adoration and action, provides intimacy and access to the transcendent, and replaces the religiosi(y and secularisation in the Church with a message of love and hope.